PENGARUH COST OF LOANABLE FUND, OVERHEAD COST DAN RISK FACTOR TERHADAP MARGIN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA (PERIODE 20013 - 2017) - ANDRIYANA, ERFA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2019)
This study aimed to examine the effect ofcost of loanable fund, overhead cost and risk factor to murabaha margin on islamic bank in Indonesia. The sample in this study consisting of 13 Islamic Commercial Bank registered in Indonesia islamic banking statistics from 2013 to 2017. This type of research is quantitative study with multiple linear regression analysis models that are processed using SPSS 23. The results of this study that Cost of Loanable Fund (COLF) has a negative effect on murabaha margins, Overhead Cost (OC) has a positive effect on murabaha margins, and Risk Factor (RF) has no effect on murabaha margins.